2015
DOI: 10.1016/j.jedc.2015.07.008
|View full text |Cite
|
Sign up to set email alerts
|

The role of bank relationships in the interbank market

Abstract: This paper empirically explores the effect of bank lending relationships in the interbank market. We use data from the e-MID market that represents the only transparent electronic platform in Europe and USA, unaffected by search costs and other fictions. We show that stable relationships exist and that they played a significant role during the 2007-2008 financial crisis. Trading with preferred counterparts is associated with more favorable rates for both lenders and borrowers, and carries larger trading volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 28 publications
3
51
0
Order By: Relevance
“…This feedback loop makes it difficult to establish the causality of the effect. Temizsoy et al (2015) shows that such feedback effects are small. Spreads do not determine survival of a bank pair into the following months once relationship indexes are controlled for, while relationship lending has an effect on spreads.…”
Section: Econometric Modelmentioning
confidence: 95%
See 3 more Smart Citations
“…This feedback loop makes it difficult to establish the causality of the effect. Temizsoy et al (2015) shows that such feedback effects are small. Spreads do not determine survival of a bank pair into the following months once relationship indexes are controlled for, while relationship lending has an effect on spreads.…”
Section: Econometric Modelmentioning
confidence: 95%
“…In addition to the abrupt topological change after Lehman defaults, mostly driven by precautionary liquidity hoarding, Cocco et al (2009), Affinito (2012, Brauning and Fecht (2012) and Temizsoy et al (2015) have shown that banks relied more extensively on relationship lending during the crisis, with both lenders and borrowers benefiting from close relationship both in terms to access to liquidity and funding rates. Relationship lending thus plays a positive role for financial stability and provides a measure of the level of financial substitutability of banks in the interbank market.…”
Section: Network Centrality and Interbank Marketsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the same dataset, in ref. (37) no impact of relationship lending on rates is found before the financial crisis. During the crisis though, and in particular after the Lehman Brothers collapse in September 2008, having relationships benefited both lenders and borrowers.…”
Section: Introductionmentioning
confidence: 96%